Dinamika Hukum Islam dalam Migrasi Transnasional Mahasiswa Muslim Indonesia di Sudan: The Dynamics of Islamic Law in the Transnational Migration of Indonesian Muslim Students in Sudan - M. Fadli; Kurniati Kurniati; Misbahuddin Misbahuddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study examines the dynamics of Islamic law in the context of the transnational migration of Indonesian Muslim students in Sudan. The interaction between Indonesian students and Sudanese Muslim society creates social and legal encounters that reflect the flexibility of Islamic law in responding to cultural and madhhab diversity. This research aims to analyze the ontological, epistemological, and axiological dimensions of Islamic law within the experiences of Muslim diaspora students in Sudan. The study employs a library research method using philosophical, normative, and socio-historical approaches to Islamic law. Primary data were obtained from classical and contemporary Islamic legal literature, while secondary data were collected from scholarly journals and studies related to transnational migration and Muslim diaspora communities. The findings demonstrate that Islamic law in the context of migration is not static, but continuously negotiates with social realities and local traditions. The use of sarong by Indonesian students and differences in qunut practices between the Shāfiʿī and Mālikī schools illustrate the adaptive and pluralistic character of Islamic law. This study contributes to the development of socio-historical studies of Islamic law by showing that Islamic law functions not only as a normative system but also as a medium for cultural adaptation, social integration, and the preservation of Muslim identity in transnational communities.